Cancer Survivors' Other Medical Problems Often Neglected (CA: a cancer journal for clinicians, 2005)
Many cancer survivors may not be getting optimal care for their other medical conditions, researchers from Boston's Dana-Farber Cancer Institute report in the journal Cancer (2004;101:1,712-1,719). In a comparison of elderly colorectal cancer survivors and healthy control subjects, the cancer survivors were significantly less likely to receive preventive care and recommended care for chronic conditions.